Modulation of P2X7 Receptor during Inflammation in Multiple Sclerosis - Amadio, Susanna; Parisi, Chiara; Piras, Eleonora; Fabbrizio, Paola; Apolloni, Savina; Montilli, Cinzia; Luchetti, Sabina; Ruggieri, Serena; Gasperini, Claudio; Laghi-Pasini, Franco; Battistini, Luca; Volonté, Cinzia (Frontiers in Immunology, 2017)
Multiple sclerosis (MS) is characterized by macrophage accumulation and inflammatory infiltrates into the CNS contributing to demyelination. Because purinergic P2X7 receptor (P2X7R) is known to be abundantly expressed on cells of the hematopoietic lineage and of the nervous system, we further investigated its phenotypic expression in MS and experimental autoimmune encephalomyelitis (EAE) conditions. By quantitative reverse transcription polymerase chain reaction and flow cytometry, we analyzed the P2X7R expression in human mononuclear cells of peripheral blood from stable and acute relapsing remitting MS phases. Human monocytes were also challenged in vitro with pro-inflammatory stimuli such as the lipopolysaccharide (LPS), or the P2X7R preferential agonist 2’3’-O-(4-benzoyl-benzoyl) adenosine5’-triphosphate (BzATP), before evaluating P2X7R protein expression. Finally, by immunohistochemistry and immunofluorescence confocal analysis, we investigated the P2X7R expression in frontal cortex from secondary progressive MS cases. We demonstrated that P2X7R is present and inhibited on peripheral monocytes isolated from MS donors during the acute phase of the disease, moreover it is down-regulated in human monocytes after pro-inflammatory stimulation in vitro. P2X7R is instead up-regulated on astrocytes in the parenchyma of frontal cortex from secondary progressive MS patients, concomitantly with MCP-1 chemokine, while totally absent from microglia/macrophages or oligodendrocytes, despite the occurrence of inflammatory conditions. Our results suggest that inhibition of P2X7R on monocytes and up-regulation in astrocytes might contribute to sustain inflammatory mechanisms in MS. By acquiring further knowledge about P2X7R dynamics and identifying P2X7R as a potential marker for the disease, we expect to gain insights into the molecular pathways of MS.